2022
DOI: 10.24042/djm.v5i1.11491
|View full text |Cite
|
Sign up to set email alerts
|

Students' problem-solving ability: An analytical practice viewed from the aspect of sociomathematical norm

Abstract: This research aims to analyze students’ problem-solving ability in terms of sociomathematical norms. Data was collected using questionnaire sociomathematical norms, ability description tests, and interviews. The total subjects in the research were six students consisting of two students with high sociomathematical norms, two students with moderate sociomathematical norms, and two students with low sociomathematical norms. In this research, there are four indicators, namely understanding the problem, planning t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
(22 reference statements)
0
3
0
2
Order By: Relevance
“…This shows that students have a good ability to understand problems, but their ability to plan, execute, and re-examine problem solving still needs to be improved. This means that students tend to have difficulty or are not confident in providing answers to check back answers in a problem (Dini & Maarif, 2022). This can affect students' ability to solve problems and find the right solution (Prastyo & Wulandari, 2023).…”
Section: Table 2 Reliability Instrument Resultsmentioning
confidence: 99%
“…This shows that students have a good ability to understand problems, but their ability to plan, execute, and re-examine problem solving still needs to be improved. This means that students tend to have difficulty or are not confident in providing answers to check back answers in a problem (Dini & Maarif, 2022). This can affect students' ability to solve problems and find the right solution (Prastyo & Wulandari, 2023).…”
Section: Table 2 Reliability Instrument Resultsmentioning
confidence: 99%
“…Earlier literature on social and sociomathematical norms focused on, among others, their development (McClain & Cobb, 2001), establishing patterns of interactions (Roy et al, 2014) and how the norms are identified (Güven & Dede, 2017) in mathematics classrooms. Recent studies link sociomathematical norms with mathematical learning and teaching experiences like self-efficacy (Apsari et al, 2020), early numeracy learning (Morrison et al, 2021), abilities in problem-solving (Dini & Maarif, 2022), mathematical process skills (Gülburnu & Gürbüz, 2022), mathematical modelling activities (Yenmez & Erbaş, 2023), and teacher noticing (Baki & Kilicoglu, 2023). This article follows these trends and explores how transforming existing sociomathematical norms enhances learners' proficiency in mathematics.…”
Section: Contribution To the Literaturementioning
confidence: 99%
“…Berdasarkan beberapa metode yang telah dilakukan mampu didapati bahwasannya setiap individu yang memiliki kemampuan berpikir kreatif matematis yang tinggi maka akan mempunyai aspek norma sosiomatematik yang tinggi pula, sejalan dengan penelitian (Dini & Maarif, 2022) mengatakan bahwasannya peserta didik dengan norma sosiomatematik yang tinggi maka kemampuan pemecahan masalahnya akan tinggi pula. Berdasarkan penelitian (Aslamiah, 2018) juga mengakatan bahwasanya norma sosiomatematik berkolerasi positif dengan prestasi belajar matematika yang terdapat pada setiap individu, atau dapat dikatakan semakin tinggi norma sosiomatematik maka semakin tinggi pula prestasi belajar matematika yang dipunyai oleh setiap peserta didik, sesuai dengan hasil penelitian yang telah didapat bahwasannya subjek yang mempunyai kemampuan berpikir kreatif yang tinggi aspek norma sosiomatematik yang dimiliki juga tinggi, dan memiliki prestasi yang cukup baik juga di dalam kelasnya.…”
Section: Subjek Dengan Kemampuan Berpikir Kreatif Matematis Rendah (S3)unclassified